The spectral analysis of syllables in patients using dentures. - Jindra, Petr; Eber, Miroslav; Pesak, Josef (Biomedical papers, 2002)
Changes in the oral cavity resulting from the loss of teeth and the ensuing reconstruction of a set of teeth by dentures (partial or complete) may cause changes in the speech and voice of the patient. The aim of the present investigation was to study the changes in speech and voice in patients suffering from teeth loss and the degree of speech improvement using dentures. Voice and speech parameters of a set of tested syllables were analysed in 10 patients at the 2nd Clinic of Stomatology. The analysis was carried out by means of an FFT, SoundForge 5.0 programme. Differently expressed acoustic changes in both consonants and vowels were ascertained in a percentage of the patients under examination. These concerned especially the sibilant ("s", "s"), labiodental ("f", "v") and vibrating ("r", "r") consonants. Changes in the FFT spectrum and air leakage in constrictive consonants were also found. In some patients the vowels, especially the closed ones ("i", "u"), may change their fundamental frequency and show noise admixture manifested as a blurred delimitation of the formants. A denture should, inter alia, render it possible for the patient to produce the same articulation to which he/she had been accustomed before the loss of teeth. For the construction of dentures the most important factors from a phonetic point of view appear to be the following: overbite, overjet, the height of the plate, the thickness of the palatal material, the incisor position, and the modelling of the ruga palatina on the hard palate. In case of wrong denture construction the acoustic changes may continue, resulting in the patient's stress load dependent upon sex, age, psychic condition and seriousness of the problem.
Keywords: Dentures / Speech / Voice